Aerobic Exercise Improves Cognitive Function in Sedentary Young Adults Without Cognitive Impairment - Sari Triyulianti; Yose Rizal; Afifah Dwi Tifani (POLTEKKES KEMENKES PONTIANAK, 2024)
Physical exercise can improve cognitive function of older adults, but the influence of young adults is less clear. The purpose of this study was to assess the effect of aerobic exercise on cognitive function of sedentary young adults without cognitive impairment. This study used an experimental method with pre and post test designs on 20 young adults according to the inclusion and exclusion criteria. Samples were randomly divided into two groups, the control group and the aerobic exercise group. The control group did not do the exercise. The aerobic group exercised by running for 30 minutes (64-76% of maximal heart rate), three time per week for four weeks. Cognitive function was measured using stroop task test. The results showed that there was a significant increase in cognitive function in the aerobic exercise group (p<0.05). There was a significant difference in cognitive function between the aerobic exercise group and the control group (p<0.05). In conclusion, aerobic exercise over four weeks can increase cognitive function in sedentary young adults without cognitive impairment.